Supreme emergency : how Britain lives with the bomb. - Corbett, Andrew (Manchester University Press, 2022)
An insider's view of the development of the UK nuclear deterrent which suggests that an aversion to the moral issues associated with civilian casualties has led to an enduring Government reticence on nuclear deterrence policy.